IMPLEMENTING THE INTEGRAL DIFFERENTIAL ESTIMATION CRITERION OF COMPETENCE ACQUISITION - Y. I. Kon; V. I. Freyman; A. A. Yuzhakov (Russian State Vocational Pedagogical University, 2015)
The paper investigates the urgent issue of education outcomes estimation in the higher school, and reveals the current approaches to solving the problem of level estimation regarding the particular competences and their components - the elements of disciplinary competences.The level model of the competence components formation and acquisition is recommended along with the computation method for weight estimation of disciplinary components by means of integral differential criteria of education outcomes assessment. The examples of and practical recommendations for the above method application are given. In authors' opinion, implementation of the given model combined with available instrumental and methodological means can raise the quality of education based on the competence approach.The paper is addressed to university teachers, methodologists and education quality experts in vocational universities.